Digital workplace in the Somogy County Pedagogical Service during an emergency: an opportunity or difficulty? - Szigeti, Mónika (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The study provides an overview of the institutional system of education service centers, their scope, and in particular, the operation of Somogy County Education Service Center. The actuality of this overview is due to the COVID-19 pandemic and its influence on the work of education service centers. We present the related laws, called “digital work schedule” including the rules of the transition to this schedule, the new methodology of care, the change of the number of supported people in Somogy County, the particularities, and the specific difficulties in different professional fields. In addition to the difficulties caused by the situation, our study also highlights the positive changes.